O contexto histórico-cultural da criação literária em Agostinho Neto: memória dos anos cinquenta - Mourão, Fernando Augusto Albuquerque (África, 1992)
This work deals with the first years spent by Agostinho Neto in Portugal as a student, firstly in Coimbra and then in Lisbon. It points out Agostinho Neto’s cultural activities and in a certain way, his political activities, emphasizing his mental universe, that includes various origins.